2009
DOI: 10.1074/jbc.m109.025155
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of ErbB3/ErbB2 Signaling by Immunoglobulin-like Necl-2

Abstract: ErbB2 and ErbB3, members of the EGF receptor/ErbB family, form a heterodimer upon binding of a ligand, inducing the activation of Rac small G protein and Akt protein kinase for cell movement and survival, respectively. The enhanced ErbB3/ ErbB2 signaling causes tumorigenesis, invasion, and metastasis. We found here that the ErbB3/ErbB2 signaling is regulated by immunoglobulin-like Necl-2, which is down-regulated in various cancer cells and serves as a tumor suppressor. The extracellular region of ErbB3, but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 46 publications
2
76
0
1
Order By: Relevance
“…Recently, several studies demonstrated that cell adhesion molecules, such as NCAM or CADM1, interact with receptor thyrosine kinases and modify their signaling. 38,39 In addition, loss of merlin and 4.1B protein, as well as CADM1, is shown to be deeply involved in the development and progression of meningiomas.…”
mentioning
confidence: 99%
“…Recently, several studies demonstrated that cell adhesion molecules, such as NCAM or CADM1, interact with receptor thyrosine kinases and modify their signaling. 38,39 In addition, loss of merlin and 4.1B protein, as well as CADM1, is shown to be deeply involved in the development and progression of meningiomas.…”
mentioning
confidence: 99%
“…The ErbB-RAC-AKT pathway, influenced by IGSF4 interaction with ErbB3, could also be of interest for leukemias, because this pathway is linked to proliferation and apoptosis. 27 We found that IGSF4 was mainly and most apparently expressed in monoblastic t(9;11)-rearranged patients. Because this subgroup of MLL-rearranged pediatric AML has recently been identified as important prognostic group, 10 the role of IGSF4 deserves further attention.…”
Section: Discussionmentioning
confidence: 70%
“…Loss of IGSF4 expression resulted in AKT pathway stimulation, which resulted in improved cell movement and survival. 27 We could not confirm similar pathway activation in our pediatric AML dataset by using microarray analysis (data not shown). In nonsmall cell lung carcinoma, IGSF4 was found to be located in an area with a common loss of heterozygosity.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…HER2-catalyzed tyrosine phosphorylation of HER3 was shown to be inhibited by the immunoglobuline-like cell adhesion molecule Nectin-like molecule-2 (Necl-2) [88]. This protein plays important roles in a variety of cellular functions and regulates a wide range of events from normal development to tumorigenesis [72].…”
Section: Hif-independent Regulation Of Erbb Igfr and Fgfr Family Memmentioning
confidence: 99%